Analysis of The Exercises in The Content Of Chemistry Books For The Intermediate Stage According To The Skills Of Mathematical Proficiency in Chemical Calculations - Dr. Abbas Fadhil Kadhim (Journal of College of Education, 2025)
The current study aims to determine the components of the mathematical prowess required in the exercises of the content of chemistry textbook for the fourth scientific grade, which is (conceptual assimilation, procedural fluency, strategic efficiency, adaptive reasoning and productive mathematical desire) These components were identified with a number of paragraphs of (26) paragraphs, and a sample was formed The research of chemistry book chapters for the first and second semester, as the number of exercises reached (106) exercises, and the study reached to identify the components of mathematical ingenuity, the chemical calculations and their indicators as well as the results that showed the availability of mathematical ingenuity components and their indicators in medium proportions in a total manner, and different for each component, respectively Conceptual assimilation (77%), procedural fluency (72%), strategic efficiency (78%) and are considered with high availability rates, or adaptive reasoning by (49%) and productive athletic desire (45%), and these are weak ratios, and the study recommended several Recommendations and proposals, including analyzing and evaluating the content of high school chemistry textbooks and other variables.
Keywords: Analysis of exercises, content of the chemistry book, mathematical proficiency in chemical calculations.